Thermal fluid-structure interaction of PCB configurations during the wave soldering process. Issue 1 (2nd February 2015) - Abdul Aziz, M.S.; Abdullah, M.Z.; Khor, C.Y.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to investigate the thermal fluid–structure interactions (FSIs) of printed circuit boards (PCBs) at different component configurations during the wave soldering process and experimental validation. Design/methodology/approach – The thermally induced displacement and stress on the PCB and its components are the foci of this study. Finite volume solver FLUENT and finite element solver ABAQUS, coupled with a mesh-based parallel code coupling interface, were utilized to perform the analysis. A sound card PCB (138 × 85 × 1.5 mm3), consisting of a transistor, diode, capacitor, connector and integrated circuit package, was built and meshed by using computational fluid dynamics pre-processing software. The volume of fluid technique with the second-order upwind scheme was applied to track the molten solder. C language was utilized to write the user-defined functions of the thermal profile. The structural solver analyzed the temperature distribution, displacement and stress of the PCB and its components. The predicted temperature was validated by the experimental results. Findings – Different PCB component configurations resulted in different temperature distributions, thermally induced stresses and displacements to the PCB and its components. Results show that PCB component configurations significantly influence the PCB and yield unfavorable deformation and stress. Practical implications – This study provides PCB designers with a profound understanding of the thermal FSI phenomenon of the process control during wave soldering in the microelectronics industry. Originality/value – This study provides useful guidelines and references by extending the understanding on the thermal FSI behavior of molten solder for PCBs. This study also explores the behaviors and influences of PCB components at different configurations during the wave soldering process.